2019
DOI: 10.1038/s41390-019-0643-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled nitric oxide as an adjunct to neonatal resuscitation in premature infants: a pilot, double blind, randomized controlled trial

Abstract: BACKGROUND: Nitric oxide (NO) plays an important role in normal postnatal transition. Our aims were to determine whether adding inhaled NO (iNO) decreases supplemental oxygen exposure in preterm infants requiring positive pressure ventilation (PPV) during resuscitation and to study iNO effects on heart rate (HR), oxygen saturation (SpO 2), and need for intubation during the first 20 min of life. METHODS: This was a pilot, double-blind, randomized, placebo-controlled trial. Infants 25 0/7-31 6/7 weeks' gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…One approach to improving systemic oxygenation and promoting pulmonary vasodilation during transition at birth, while establishing the lung as the organ of gas exchange without excessive supplemental oxygen, is to use a selective pulmonary vasodilator such as iNO in the delivery room. In a recently published pilot double-blind randomized controlled trial on the use of inhaled nitric oxide in the delivery room resuscitation of extremely low birthweight preterm infants by Sekar et al, those who received 20 ppm iNO as an adjuvant in the resuscitation gas had a lower cumulative FiO 2 exposure and a lower rate of exposure to FiO 2 > 0.6 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One approach to improving systemic oxygenation and promoting pulmonary vasodilation during transition at birth, while establishing the lung as the organ of gas exchange without excessive supplemental oxygen, is to use a selective pulmonary vasodilator such as iNO in the delivery room. In a recently published pilot double-blind randomized controlled trial on the use of inhaled nitric oxide in the delivery room resuscitation of extremely low birthweight preterm infants by Sekar et al, those who received 20 ppm iNO as an adjuvant in the resuscitation gas had a lower cumulative FiO 2 exposure and a lower rate of exposure to FiO 2 > 0.6 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of iNO when administered through non-invasive ventilation in the delivery room is not known. However, in the pilot trial by Sekar et al, iNO was effective in reducing FiO 2 during resuscitation in the delivery room [ 18 ]. We monitored pulse oximetry but mainly relied on frequent preductal PaO 2 measurements for titrating inspired oxygen due to the variable relationship between SpO 2 and PaO 2 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no differences in the secondary outcomes measured, including IVH. This first pilot human trial suggested that the administration of iNO during resuscitation is feasible and decreased exposure to supplemental oxygen in premature infants ( 158 ). It should be noted that an acute reduction in PVR during the transition with iNO may increase the pulmonary venous return and increase organ perfusion, particularly to the brain, increasing the risk of IVH.…”
Section: Novel Ino Use In Premature Newborn Resuscitationmentioning
confidence: 99%
“…9,10 Certainly, supplemental oxygen is an essential component of the overall lifesustaining care that is provided to premature babies as part of resuscitation, but are there ways to facilitate pulmonary vasodilation and support adequate oxygenation without high levels of oxygen? Sekar et al 11 investigated the use of INO as an additional therapy during neonatal resuscitation with a double-blind, RCT of 28 infants during positive-pressure ventilation. Half were randomized to receive oxygen (F IO 2 ¼ 0.3) and INO at 20 ppm (the INO group), and the other half were randomized to receive oxygen and placebo (the control group).…”
Section: Supplemental Oxygenmentioning
confidence: 99%